In the road and the in-between: An approach between the novels Amarás a Dios sobre todas las cosas (2013), by Mexican writer Alejandro Hernández and La mara (2004), by also Mexican Rafael Ramírez Heredia - Rodrigues Lopes, Mariana (2019)
This article aims to analyze the narrative representations of the Central American migrations to the United States, as they are elaborated in the novels Amarás a Dios sobre todas las cosas (2013), by the Mexican writer Alejandro Hernández and La mara (2004), by the also Mexican Rafael Ramírez Heredia. We will focus on two topics of the greatest importance in both books to understand today’s Central America: the role played by the concept of the road for the migrant of Amarás a Dios sobre todas las cosas (2013) and the notion of in-between in La mara (2004). The reflection that we propose in this article is part of a broader discussion developed in our doctoral thesis, which focused on the Central American migrations to the United States and their representations in the contemporary narrative. These two texts are particularly interesting because they work in a different way the chronotope of the road and the notion of in-between. Both books are part of a growing body of novels whose central theme is the migratory movements in the region.